Paediatric major incident simulation and the number of discharges achieved using a major incident rapid discharge protocol in a major trauma centre: a retrospective study. Issue 12 (10th December 2020) - Bird, Ruth; Braunold, Daniel; Dryburgh-Jones, Jack; Davis, Jordan; Rogers, Sam; Sohrabi, Catrin; Ismail, Elliot; Mclean, Nina; O'neill, Breda; Edmonds, Naomi; Tallach, Rosel
Abstract : Objectives: Hospitals have the responsibility of creating, testing and maintaining major incident (MI) plans. Plans emphasise readiness for acceptance of casualties, though often they neglect discharge planning and care for existing inpatients to make room for the sudden influx. After collaboration and design of a discharge policy for a paediatric MI, we aimed to establish the number of beds made available (primary outcome) to assess potential surge and patient flow. We hypothesised that prompt patient discharge would improve overall departmental flow. Flow is vital for sick patients awaiting admission, for those requiring theatre and also to keep the emergency department clear for ongoing admissions. Method and setting: A simulated MI was declared at a London major trauma centre. Five paediatric priority 1 and 15 priority 2 and priority 3 patients were admitted. Using live bed boards, staff initiated discharge plans, and audits were conducted based on hospital bed occupancy and discharge capacity. The patients identified as dischargable were identified and folllowed up for 7 days. Results: Twenty-nine ward beds were created (42% of the total capacity). Handwritten summaries just took 13.3% of the time that electronic summaries took for the same patients by the same doctor. In-hospital transfers allowed five critically injured children into paediatric intensive care unit (PICU), and creation of a satellite PICU allowed for an additional six more if needed. Conclusion: We increased level 3 capacity threefold and created 40% extra capacity for ward patients. A formalised plan helped with speed and efficiency of safe discharge during an MI. Carbon copy handwritten discharge letters allowed tracking and saved time. Robust follow-up procedures must be in place for any patients discharged.